A pilot outcomes evaluation for computer assisted therapy for substance misuse -- an evaluation of Breaking Free Online. (August 2014) - Elison, Sarah; Humphreys, Lloyd; Ward, Jonathan; Davies, Glyn
Abstract Introduction: Computer Assisted Therapy (CAT) is an emerging treatment within addictions, though the evidence-base is still growing. Therefore, this study describes a pilot outcomes evaluation of a CAT programme for substance misuse, "Breaking Free Online". Method: A total of 34 service users using Breaking Free Online were included. Quantitative assessments of ability to cope with cravings and maintain abstinence and quality of life were conducted pre- and post-engagement treatment, and qualitative feedback was collected. Results: Significant improvements in perceived ability to control cravings and maintain abstinence were identified and improvements in quality of life were seen, with p values measuring change from baseline to follow-up ranging 0.026–<0.0001. Participants also reported drug use was either reduced or that they had become abstinent. Qualitative feedback was positive, with participants reporting engagement with the programme reduced substance use and had improved adaptive functioning. Conclusions: Data from this study indicate potential positive improvements in a number of areas of functioning, including ability to abstain and quality of life. Feedback regarding experiences of using the Breaking Free Online was positive, indicating it may provide effective treatment for substance misuse. Further qualitative research and outcome studies are now underway to examine effectiveness of the programme.